Slowdown of the Atlantic meridional overturning circulation in a coupled simulation - Iversen, Silje Christine (2020)
The Atlantic meridional overturning circulation (AMOC) is projected to weaken under global warming. This study investigates this weakening overturning and addresses the question regarding which aspects lead to such a weakening. A selection of suggestions on mechanisms which can be responsible for the AMOC weakening are presented, and the aim is to answer if the weakening is consistent with one or several of these suggestions. The study makes use of outputs from a coupled climate model participating in the Coupled Model Intercomparison Project Phase 6 (CMIP6), and the model of use is NorESM2-LM. The chosen model simulation experiences a quadrupling of the atmospheric CO2 concentration, which results in a rapid and intense global warming and a slowdown of the AMOC. The results suggest that the weakening of the AMOC is consistent with a reduction in the meridional density gradient. A reduction in the meridional density gradient is associated with a reduction of the eastward shear through the thermal wind relation, thus slowing down the eastward flowing branch of the North Atlantic Current (NAC). The weakening of this branch is communicated to the currents it is feeding and being fed by, such that the entire system of surface currents flowing northward slows down. Increased freshwater into the northern North Atlantic is the key to reducing the meridional density gradient. However, the large-scale gradient that stretches from the tropics to the northernmost regions (the subpolar gyre and the Nordic Seas) does not weaken during the very first years of AMOC weakening. Instead, a weakening of a smaller-scale gradient across the eastward flowing NAC is found. Moreover, the results suggest that changes in the local winds in the northern North Atlantic may contribute to the weakening of the AMOC by directly weakening the currents in the subpolar gyre region. This possibility has not been fully tested, and further investigation is required.